判
斷
有
理
數
▶
有
理
數
:
可
以
分
成
兩
整數
形式
的
分
數
。
所
以
有
2,
-3,
0,
,
−
,
+
√
+
√
·
−
√
−
√
=
−
√
+
√
−
−
=
▶
實
數
為
不
含
虛
數
之
值
,
以上
皆
為
實
數
。
有
理
數
無
理
數
a
−
c
=
(
d
−
b
)
√
e
,
假
設
(
d
−
b
)
不
為
零
,
則
√
e
=
a
−
c
d
−
b
為
有
理
數
矛
盾
。
假
設
(
d
−
b
)
為
零
,
即
b
=
d
,
a
−
c
=
·
√
e
⇒
a
=
c
策
略
:
找
一
反
例
,
有
反
例
則
答
案
為
否
。
(
a
,
b
,
c
,
d
)
=
(
,
,
+
√
,
√
)
x
+
√
x
+
y
−
√
y
=
−
√
等
式
整
理
⇒
(
x
+
y
−
)
+
(
x
−
y
+
)
√
=
⇒
(
x
−
y
+
)
=
,
否
則
√
=
(
x
+
y
−
)
(
x
−
y
+
)
為
有
理
數
矛
盾
。
(
x
+
y
=
x
−
y
=
−
⇒
(
x
,
y
)
=
(
,
)
有
理
數
直
接
證
法
▶
(
a
+
b
=
p
a
−
b
=
q
⇒
p
,
q
∈
Q
計
算
(
a
,
b
)
,
形式
要
是
p
,
q
組
成
計
算
b
a
+
b
=
(
p
−
q
)
⇒
a
=
(
p
−
q
)
−
b
代
入
第
二
式
p
−
q
−
b
−
b
=
q
⇒
p
−
q
=
b
⇒
b
=
p
−
q
計
算
a
,
由
第
二
式
變
換
a
=
q
+
b
代
剛
得
出
來
的
b
a
=
·
p
+
q
=
p
+
q
▶
∵
p
∈
Q
,
q
∈
Q
,
q
∈
Q
⇒
p
+
q
∈
Q
⇒
p
+
q
∈
Q
∴
a
∈
Q
∵
p
∈
Q
,
q
∈
Q
⇒
p
−
q
∈
Q
⇒
p
−
q
∈
Q
∴
b
∈
Q
▶
a
+
b
,
a
−
b
∈
Q
Pf.
(
a
+
b
)
+
(
a
−
b
)
∈
Q
∵
a
,
b
∈
Q
∴
a
+
b
∈
Q